Brillouin-raman multi-wavelength laser comb generation based on BI-EDF by using dual-wavelength in dispersion compensating fiber - Shahi, S.; Harun, Sulaiman Wadi; Norizan, S.F.; Moghaddam, M.R.A.; Ahmad, Harith (World Scientific Publishing, 2010)
A multi-wavelength Brillouin fiber laser (BFL) is demonstrated by using dual-wavelength fiber in a 7.7km dispersion compensating fiber (DCF) that is incorporated in a 49 cm Bismuth erbium-doped fiber laser. The BFL operates in C-band, which is shifted by 0.08nm and amplified by a Raman pump (RP). The threshold power for BP pumps and the Raman pump is achieved at 7dBm and around 35mW, respectively. The exclusive and practical benefits of using reduced high nonlinear Bismuth-erbium doped fiber (Bi-EDF) in implementing a four-wave mixing (FWM) method for multi-wavelengths Brillouin fiber laser (BFL) applications are experimentally demonstrated. Coupled interactions of Brillouin, Raman, and FWM scattering explain the unique feature of proposed configuration.